Implementasi Perancangan Digital Marketing pada Instagram Rumah Makan Bebek Bakar A’Yayo - Putra, Omega Marthadania; Shabrina, Almira (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research explores how improving Instagram marketing strategies can boost consumer interest for Bebek Bakar A’Yayo, a restaurant in Bandung. Despite being established since 2005, the restaurant’s social media presence had been minimal. Using a mixed-method approach—surveys, interviews, and observations—the author enhanced the restaurant’s Instagram with better photos, videos, graphic design, and motion graphics. Over two months (October 23 to December 25, 2023), the Instagram account’s reach grew by 602%, and sales increased by 20%, all through organic social media efforts. The study concludes that effective Instagram management is essential for promoting businesses in the food industry.